2020
DOI: 10.3390/foods9121859
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Chia, Quinoa and Amaranth Incorporation on the Physico-Chemical, Nutritional and Functional Quality of Fresh Bread

Abstract: With regard to constant technological innovations in the bakery sector in order to increase bread nutritional value without affecting its technological and sensory characteristics, we applied pseudocereals/oilseeds to obtain an optimal formulation. A factorial design 33 was used and the independent factors were chia flour (levels: 0, 10, 20% flour basis), quinoa flour (levels: 0, 20, 40% flour basis), and amaranth flour (levels: 0, 20, 40% flour basis). Their effects and interactions were studied through the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 74 publications
3
17
0
Order By: Relevance
“…As compared to earlier bread prototypes containing non-sprouted pseudo-cereal grains, the breads developed in this study had lower PA levels than 10% chia, 4% quinoa and 20% amaranth bread (3.4 g/100 g dw) [ 29 ].…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…As compared to earlier bread prototypes containing non-sprouted pseudo-cereal grains, the breads developed in this study had lower PA levels than 10% chia, 4% quinoa and 20% amaranth bread (3.4 g/100 g dw) [ 29 ].…”
Section: Resultsmentioning
confidence: 82%
“…Overall, lower nutritional value of WF as compared to sprouted pseudo-cereal grains could be attributed to the removal of bran outer layers and germ during the refining process of wheat flour [ 29 ]. In these anatomical parts of wheat grain, nutrients such as fat, dietary fiber, PA, minerals, vitamins and antioxidant compounds (bound phenolic acids) are concentrated so that they are lost during flour production.…”
Section: Resultsmentioning
confidence: 99%
“…The specific volume of the GFC determined in the present study was similar to the results reported previously [ 26 ]; however, in comparison with wheat bread, the value of this parameter was meaningfully lower [ 37 ]. A specific volume of a conventional wheat bread ranged from 3.5 to 5.5 cm 3 /g [ 38 , 39 ], while its value for GF was meaningfully reduced and fluctuated around 2 cm 3 /g, depending on the ingredients used [ 26 , 40 ]. The use of BLP in the experimental GF formulation influenced the technological parameters of GFB.…”
Section: Resultsmentioning
confidence: 99%
“…Chia seeds, as a valuable and increasingly popular component of "healthy food", have been the focus of previously published review articles [6,9,[31][32][33][34][35][36][37][38][39]. The authors emphasized the importance of chia seeds as a valuable new food resource with high health and antioxidant potential.…”
Section: Introductionmentioning
confidence: 99%